Social Media and Outbound Ticket Sales: Examining Social Media Strategies Among Top-Performing Salespeople - Clint Warren (Journal of Applied Sports Management, 2016)
This paper examines current implementation of social media strategies by ticket salespeople. A sample of 126 ticket sales professionals across professional, collegiate, and minor league sport responded to a survey measuring social media usage rates across a variety of platforms, social media use throughout the sales process, and sales performance. Results indicate that overall ticket salespeople are not incorporating social media into their regular sales initiatives. However, top-performing sales professionals do tend to use social media more regularly than baseline ticket sales representatives when approaching and discovering the needs of their customers. Given the rise of social media as a business-to-business communication medium, ticket sales managers should consider incorporating more training and empowering their salesforces to leverage social media to facilitate greater sales success.
Keywords: Social media; ticket sales; sales performance; sales management